ANALISIS IMPLEMENTASI PERMENDAGRI N0 04 TAHUN 2010 TENTANG PELAYANAN ADMINISTRASI TERPADU KECAMATAN (PATEN) (Studi Kasus di Kecamatan Bunguran Timur Kabupaten Natuna Tahun 2014 – 2015) - Eka Rizqi Yudandewi (MIP UMY, 2016)
Bad image of public services in Indonesia in the past already attached in the wider community. The slowness of service, difficult and complex requirements that must be met and the lack of transparency in the issue of financing raises people's reluctance to manage licensing The concept of the District Integrated Administrative Service (PATENT) is provision of administrative services in the district from the proposal stage to stage until the publication of documents in one place. Background Implementation PATENT in District East Bunguran geographical conditions Natuna regency. PATENT policy line NATUNA Vision and Mission District. This study aims to determine how the implementation Bunguran PATENT in District East, as well as any factors that inhibit and PATENT Implementation supporting factors in the district of East Bunguran. The method used is Mix metod, the location of the research conducted in the District Bunguran East Natuna regency, Collecting data in this study using the technique of questionnaires, interviews, and observation. Research found that the stages of implementation in the district of East Bunguran PATENT implemented in accordance with the standards of service PATENT. It can be seen from the quality of services provided by the clerk to the public PATENT. PATENT Implementation supporting factors, namely the government's commitment that want to provide excellent public services and quality. In addition, the support of the community. Inhibiting factor is not the availability of services PATENTS complaint, and not optimal socialization in the form of brochures, banners and Internet networks in the district of East Bunguran. Thus the results of this study recommend to the District Government East Bunguran to Enhancing infrastructure and optimal socialization.